ANALYSIS THE MASTERPIECE BY IMAM AL-ZAMAKHSHARI: A Study of Methodology and Interpretation on Tafsir Al-Kasyaf - Abdulloh Labib (STAI ALHIKMAH Jakarta, 2023)
AbstrakArtikel ini memberikan wawasan bahwa tafsir al-Kasyaf merupakan salah satu tafsir yang sangat bagus jika di nilai dalam segi bayan, balaghah dan aspek mukjizat lainnya dari al-Qur’an. Kedalaman ilmu dan kemampuan kebahasaan yang dimiliki oleh al-Zamakhsyari mampu mengeluarkan wajah baru serta keindahan al-Qur’an. Penelitian ini akan mengkaji perihal metodologis tafsir al-Kasyaf dan karakteristik penafsiranya. Hasil penelitian menunjukkan bahwa pandangan al-Zamakhsyari lewat tafsir al-Kasyaf sangat dipengaruhi oleh konteks yang melatarbelakangi lahirnya tafsir ini, hal ini bisa dilihat ketika berbicara mengenai masalah teologi dalam tafsirnya, maka akan terlihat dengan jelas bahwa al-Zamakhsyari membela prinsip aliran Mu’tazilah. Meskipun banyak ajaran mu'tazilah di dalamnya, hal itu merupakan konsekuensi logis dari ideologi mufassir.AbstractThis article provides an insight that the interpretation of al-Kasyaf is very good interpretation if it is assessed in terms of bayan, balaghah and other miraculous aspects of the Qur'an. The depth of knowledge and linguistic ability possessed by al-Zamakhsyari can bring out a new face and the beauty of the Qur'an. This study will examine the methodological issues of al-Kasyaf's interpretation and the characteristics of its interpretation. The results of the study show that al-Zamakhsyari's view through the interpretation of al-Kasyaf is greatly influenced by the context that is the background for the birth of this interpretation, this can be seen when talking about theological issues in his interpretation, it will be seen clearly that al-Zamakhsyari defends the principles of the Mu'tazilah sect . Even though there are many mu'tazilah teachings in it, this is a logical consequence of the mufassir's ideology.